THE FORGOTTEN INDEX OF CERTAIN EDGE-GLUING GRAPHS - Ahmed M. Salih; Nabeel E. Arif (Tikrit Journal of Pure Science, 2023)
The forgotten index is defined as ( ) ∑ ( )( ) . Where ( ) is a degree of vertex . In this paper, we study certain known graphs such as cycle, complete, wheel, and web graphs, then computed the forgotten index of their edge-gluing graphs